MP44: Implementing rural advanced care community paramedics in rural and remote British Columbia: a qualitative research approach. (May 2020) - Besserer, F.; Banner-Lukaris, D.; Tallon, J.; Kandola, D.
Abstract : Introduction: Community paramedicine is well-established with an increasing evidence base to support its role in improving healthcare delivery in Canada and across the world. In British Columbia (BC), the BC Emergency Health Services (BCEHS) community paramedicine program provides an avenue to expand the Advanced Care Paramedic (ACP) role in underserved rural and remote communities across the province. Methods: We undertook stakeholder consultations using purposive sampling to better understand the barriers and facilitators impacting the integration of rural advanced care community paramedics (RACCPs) in 6 BC communities and to evaluate stakeholder perspectives of the implementation and impacts of the RACCP. 18 in-depth interviews were completed with a diverse range of stakeholders. The interviews were analyzed using a qualitative descriptive approach and the Theoretical Domains Framework. Results: A number of key facilitators and barriers to implementation of the RACCP were identified. Facilitators included the RACCP bridging significant gaps in existing community-based healthcare services including palliative care, harm reduction, and home-based assessment. The RACCP also provides leadership within their communities by actively engaging in the delivery of informal and formal debriefing, mentorship, and education. Identified barriers to RACCP implementation included confusion over the scope of the RACCP role, lack of shared health data, and various regulatory challenges. Several priority areas for ongoing development were also identified including workforce planning, addressing regulatory requirements, developing a strategic and systematic activation and dispatch process, providing continuing mentorship and supports for RACCPs, and the importance for ongoing engagement with end-users to determine the impact of the RACCP role for community health services. Conclusion: This research provides a strong foundation for addressing healthcare delivery in rural and remote BC by identifying the unique challenges communities face in healthcare provision and is a leading initiative for the ongoing development of professional paramedic practice across the province.